Cyclic Voltammetric Study of High Speed Silver Electrodeposition and Dissolution in Low Cyanide Solutions - Bo Zheng; Lai Peng Wong; Linda Y. L. Wu; Zhong Chen (International Journal of Electrochemistry)
The electrochemical processes in solutions with a much lower amount of free cyanide (<10 g/L KCN) than the conventional alkaline silver electrolytes were first explored by using cyclic voltammetry. The electrochemical behavior and the effect of KAg(CN)2, KCN, and KNO3 electrolytes and solution pH on the electrodeposition and dissolution processes were investigated. Moreover, suitable working conditions for high speed, low cyanide silver electrodeposition were also proposed. Both silver and cyanide ions concentration had significant effects on the electrode polarization and deposition rate. The onset potential of silver electrodeposition could be shifted to more positive values by using solutions containing higher silver and lower KCN concentration. Higher silver concentration also led to higher deposition rate. Besides maintaining high conductivity of the solution, KNO3 might help reduce the operating current density required for silver electrodeposition at high silver concentration albeit at the expense of slowing down the electrodeposition rate. The silver dissolution consists of a limiting step and the reaction rate depends on the amount of free cyanide ions. The surface and material characteristics of Ag films deposited by low cyanide solution are also compared with those deposited by conventional high cyanide solution.